Quantitative evaluation of urban resilience in underdeveloped regions: a study of six cities in Sichuan & Tibet, China - Zhou, Rui; Yu, Yang; Wu, Bingxia; Luo, Xunrui (Frontiers in Environmental Science, 2023)
Urban resilience construction can aid in the management of urban crises and enhance the quality of the human living environment. Compared to metropolises in developed regions, cities in underdeveloped regions with unsatisfactory natural environments, insufficient economic and social development, and inadequate infrastructure construction are highly vulnerable to challenges posed by natural disasters, epidemics, and climate change. Comprehensive quantitative evaluations are needed to identify avenues for enhancing urban resilience. This study employs the TOPSIS entropy weight method and coupled coordination model to evaluate the economic, social, environmental, and infrastructure resilience of six cities and states along the Sichuan-Tibet Railway in China from 2015 to 2020. Furthermore, correlation and gray correlation analysis are used to identify the primary factors influencing the urban resilience of underdeveloped regions. The findings are as follows. Firstly, during 2015-2020, the overall urban resilience of each city and state maintained an increasing trend, with different trends in the evolution of the four resilience indices and differences among cities, and the highest overall resilience is in Lhasa. Secondly, the coupling coordination between the overall resilience and each resilience aspect maintained an increasing trend and differed significantly from each other. Finally, the social and economic resilience of each city and state maintained an increasing trend and differed significantly from each other. On this premise, we present a three-dimensional evaluation model for analyzing the evolutionary trajectories and resilience patterns of cities. This work intends to present new concepts for assessing and optimizing urban resilience in underdeveloped regions using quantitative methodologies, as well as providing references for urban resilience construction in these places.